The Impact of Private Provision of Public Education : Empirical Evidence From Bogota's Concession Schools - Barrera, Felipe (The World Bank, 2007)
In 1999 the city of Bogota, Colombia launched the concession school program designed to broaden the coverage and quality of basic education. It consists of a contract between a group of private schools and the public educational system such that private agents provide education for low-income students. This paper tests three main hypotheses concerning the impact of concessions on the quality of education: first, dropout rates are lower in concession schools than in similar public schools; second, other public schools nearby the concession schools have lower dropout rates in comparison with other public schools outside the area of influence; and third, test scores from concession schools are higher than scores in similar public schools. The paper presents evidence in favor of the three hypotheses using propensity score and matching estimators